Konstruksi Teologi Pembebasan dalam Islam: Studi Pemikiran Asghar Ali Engineer: The Construction of Liberation Theology in Islam: A Study of Asghar Ali Engineer's Thought - Negara, Muhammad Adres Prawira (Dirasat Islamiah: Jurnal Kajian Keislaman, 2023)
Islam is a religion that upholds the values of justice. However, Muslims today have undergone a total change and ignored these values. The theology of liberation formulated by Asghar Ali Engineer is a necessity to awaken Muslims from boredom and realize the values of justice inherited by the Prophet Muhammad SAW. In addition, liberation theology has become a critique for traditional scholars who only prioritize metaphysical issues and ignore humanitarian issues. Thus, this research was appointed to describe in depth the theology of liberation constructed by Asghar Ali Engineer. The method used in this research is a qualitative method based on a literature study. The results of this study are the construction of Asghar Ali's theology of liberation, which covers three points: monotheism, which is interpreted as human unity; a movement that must be based on a strong faith to fight for justice and fight against unjust rulers; and justice in the economic field to free the small people who are exploited by the capitalist system.